Botanical imagination rethinking plants in modern Japan - Pitt, Jon L. ca. 21. Jh (Cornell University Press, 2025)
"This book examines Japanese writers and filmmakers who have responded to moments of crisis in Japan's modern period by imagining what it would mean for humans to be more like plants."--
Keywords: Japanese literature / 20th century / History and criticism; Japanese literature / 21st century / History and criticism; Plants in literature; Motion pictures / Japan / History; Plants in motion pictures; Human ecology / Japan; Littérature japonaise - 20e siècle - Histoire et critique; Littérature japonaise - 21e siècle - Histoire et critique; Plantes dans la littérature; Cinéma - Japon - Histoire; Plantes au cinéma; Literary criticism; Film criticism; Critiques littéraires; Critiques cinématographiques